IMPLEMENTASI KODE ETIK JURNALISTIK PADA FOTO JURNALISTIK DALAM RUBRIK HUKUM KRIMINAL DI PORTAL BERITA RIAUAKTUAL.COM - Herdi Amdika Deap; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Journalistic Code of Ethics is a directions for journalists in carrying out their duties and responsibilities. The riauaktual.com news portal still uploads photos of the faces of crimes without disguising the faces of their identities which violates the rules of the Journalistic Code of Ethics. This study aims to determine the implementation of the journalistic code of ethics on photojournalism in the hukum kriminal rubric on the riauaktual.com news portal based on the theory of social responsibility as well as the obstacles encountered in the implementation of this journalistic code of ethics.This research uses descriptive analysis with a qualitative approach. The subjects involved in this study were determined using a purposive sampling technique consisting of the Editor in Chief of riauaktual.com, the Chairman of the Pekanbaru regional Aliansi Jurnalis Indonesia (AJI), the Chairman of the Pekanbaru Regional Pewarta Foto Indonesia (PFI), the riauaktual.com journalist and 2 (two) readers. The data analysis technique used interactive model analysis by Miles and Huberman.The results showed that from January to March 2020 there was a journalistic code of ethics which was associated with presumption of innocence. Displays 13 journalistic photo uploads showing the face of the suspect without disguised so that his identity can be easily identified. The news portal riauaktual.com was inconsistent in its uploads, which is there were photos that matched with journalistic code as a presumption of innocent and some were not. There is negligence and lack of control over news uploads on the riauaktual.comnews portal. Obstacles in implementing this journalistic code of ethics include the lack of control over news uploads on riauaktual.com the news portal, journalists who are negligent in carrying out the journalistic code of ethics and weak sanctions for violations of journalistic code of ethics  Keywords: implementation, Journalistic Code of Ethics, Photo Journalism, riauaktual.com news portal, theory of social responsibility